EUROPEAN SECURITY ISSUES AS SEEN BY POLISH PARLIAMENTARIANS - MALINOWSKI, Krzysztof; NOWOSIELSKI, Michał (Przegląd Strategiczny, 2018)
The article attempts to explore the views of the Polish parliamentarians on threats to the security of Europe and the EU and their implications for Poland and its relations with Germany in the context of the Ukrainian conflict, NATO transformations, divergent energy interests and the refugee crisis. We follow the hypothesis, that the opinions on the threats and conflicts in the neighborhood of Europe were consistent across party lines in Europe’s neighborhood and they suggest a strong consensus on the necessity to strengthen the cooperation in NATO. The article examines the responses of members of the Polish parliament (members of parliamentary committees on foreign and European affairs and security, members of the Polish-German parliamentary group) and all Polish members of the European Parliament to a dual survey carried out in 2015 and 2016. The questionnaire was completed by 22 respondents in the first and 21 respond ents in the second survey. The respondents represented diverse political parties (Civic Platform, Law & Justice, Democratic Left Alliance, Polish People’s Party).